A refinement of the Poincaré inequality for Kolmogorov operators on ℝd. Issue 1 (1st February 2005) - Fujita, Yasuhiro
Abstract : We give a refinement of the Poincaré inequality for Kolmogorov operators onℝ d . This refinement yields some regularity result of the corresponding semigroups.